Membangun Identitas Budaya melalui Bahasa: Analisis Konstruksi Sosial Berger dan Luckmann dalam Cerita Menara Babel Kejadian 11: 1–9 - Yolanda Palar; Vinkan Anggita Janis (DA'AT : Jurnal Teologi Kristen, 2024)
This research aims to describe the role of language in building social identity in the Tower of Babel narrative (Genesis 11: 1-9) using the analytical framework of Berger and Lucmann's (1966) social construction theory. The focus of this research is the description of human ambition to build a tower that can reach the sky which ultimately causes division and language diversity. Based on the analysis using Berger and Lucmann's social construction theory in Genesis 11: 1-9 shows that language can be a unifying tool, a builder as well as a destroyer and inhibitor of a nation's cultural identity. It can be said that language becomes the main tool in the process of forming cultural identity, both individual and collective. The analysis of the Tower of Babel story highlights the complexities in social and linguistic interactions that shape and reconstruct cultural meaning in the context of social construction theory.